Self-organization in the commons: An empirically-tested model. (October 2017) - Ghorbani, Amineh; Bravo, Giangiacomo; Frey, Ulrich; Theesfeld, Insa
Abstract: A appropriate bottom-up rule system can support the sustainability of common-pool resources such as forests and fisheries. The process that leads to the developments of such institutional settings requires the considerations of multiple social, physical, and institutional factors over long time horizons. In this paper, we present the SONICOM model as a general exploratory model of CPR systems. The model can be configured to represent different CPR systems in order to explore what kind of institutional settings result in stable systems, i.e. situations where the resource and the appropriators are in a state of well-being. We use a large-N-dataset of CPR management institutions to validate the model. The results show numerous correlations between various parameters of the system such as rule compliance, social influence and resource growth rate which help explaining the process of institutional emergence as well as unveiling the conditions under which systems are stable. Highlights: Endogenous institutions can help the self-organization and sustainability of common-pool resource systems. Simulation models can be used to study endogenous institutions and their characteristics. The SONICOM simulation model of endogenous institutions has been theoretically and empirically validated. SONICOM is a virtual lab to study institution in different CPR setting after adding case specific data to the model.